Tensile Characterization of Porcine Temporomandibular Joint Disc Attachments - Murphy, M.K. (SAGE Publications, 2013)
The frequency and impact of temporomandibular joint (TMJ) disorders necessitate research in characterizing the joint’s function. The 6 discal attachments have not yet been systematically characterized under tension. Understanding their role in joint function may guide our study of TMJ pathologies, including disc displacement. In the present study, a porcine model was used to characterize the attachments in tension anteroposteriorly and mediolaterally, based on previously identified similarities in the porcine and human masticatory behaviors and discal properties. Tensile stiffness, strength, toughness, and maximum strain were quantified. Collagen alignment was characterized via polarized light and scanning electron microscopy. Anisotropy was demonstrated in all attachments, with the exception of the anterior inferior attachment. Anteroposteriorly, the lateral attachment was stiffest (8.3 MPa) and the anterior superior was least stiff (1.4 MPa). Mediolaterally, the posterior superior attachment was stiffest (16.3 MPa) and the medial was least stiff (1.4 MPa). The greatest strain was observed in the lateral attachment in the mediolateral direction and the posterior superior attachment in the anteroposterior direction. With greatest strains in the most commonly observed directions of disc displacement, it is suggested that compromise in the posterior and lateral attachments contributes to partial lateral and anterior disc displacement.